Aesthetic effect evaluation of the xenogeneic collagen matrix in keratinized mucosa augmentation around dental implants - YANG Yan; ZHANG Jia; MA Xuechun; CAI Andong; ZHOU Wenjuan; LIU Zhonghao (口腔疾病防治, 2024)
Objective To evaluate the stability and aesthetic effect of a xenogeneic collagen matrix (mucograft) on achieving an adequate keratinized mucosa width (KMW) around implants and to provide a reference basis for the clinical application of xenogeneic collagen matrix materials. Methods The hospital ethics committee approved the study protocol, and the patients provided informed consent. Twenty patients with a KMW<2 mm at the buccal implant site who were treated in Binzhou Medical University Affiliated Yantai Stomatological Hospital from July 2020 to September 2022 were included, and a total of 36 implants were included. The mean age of the patients was (52.0±10.4) years, of which 18 were females and 2 were males. They were divided into a free gingival graft group (FGG, control group) and a xenogeneic collagen matrix group (test group) according to different graft materials. The incremental effect of the KMW on the buccal side of the implant and the mucosal shrinkage rate was measured at 1 month and 3 months after the operation. The mucosal scar index (MSI) was evaluated after the operation. Results At 3 months postoperatively, the KMW was (3.67 ± 1.06) mm in the control group and (2.96 ± 0.98) mm in the test group, and the difference was statistically significant (t = 2.076, P<0.05). The KMW shrinkage rate was (33.34 ± 16.30) % in the test group and (22.05 ± 15.47) % in the control group at 1 month postoperatively and (51.95 ± 12.60) % in the test group and (37.44 ± 16.30) % in the control group at 3 months postoperatively, with statistically significant differences between the two groups at the same time points (P<0.05). Three months after surgery, the test group showed significantly better outcomes than the control group in terms of the five scar indicators (scar width, scar convexity, scar color, scar trace, and overall appearance), and the difference was statistically significant (P<0.05). Conclusion Xenogeneic collagen matrix can increase the peri-implant KMW and achieve a more natural and coordinated soft tissue aesthetic effect but with a higher shrinkage rate.